2021
DOI: 10.1007/s12262-021-02972-2
|View full text |Cite
|
Sign up to set email alerts
|

Glut 1, S-100, and Nerve Bundle Study in Vascular Anomalies

Abstract: Vascular anomalies grouped into vascular tumors (hemangioma) (HI) and vascular malformation (VM) are benign vascular lesions that are difficult to distinguish from one another clinically and often confused with each other at histopathology. This confusing terminology leads to improper diagnosis, illogical treatment, and misdirected research. This study aimed to study GLUT 1, S-100, and nerve bundle to differentiate hemangioma and vascular malformation. Thirty two cases of vascular lesions (26 vascular malforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…On comparing our study with other similar studies conducted in India, such as the studies of Rangabashyam et al, 5 Shukla and Kumar, 6 Khanna et al, 7 and Iyer and Gore, 8 we found a similarity in the incidence of fibroadenoma and fibroadenosis. The two groups of BBDs, i.e., fibroadenoma and fibroadenosis, constitute more than 78% of all BBDs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On comparing our study with other similar studies conducted in India, such as the studies of Rangabashyam et al, 5 Shukla and Kumar, 6 Khanna et al, 7 and Iyer and Gore, 8 we found a similarity in the incidence of fibroadenoma and fibroadenosis. The two groups of BBDs, i.e., fibroadenoma and fibroadenosis, constitute more than 78% of all BBDs.…”
Section: Discussionsupporting
confidence: 81%
“…Incidence of breast abscesses, breast cysts, galactoceles, and lipoma cases are comparable to other Indian studies, whereas mastalgia is not comparable to studies conducted by Shukla and Kumar and Khanna et al 6,7 and Krishnaswamy, 9 wherein mastalgia was the most common presentation of BBDs.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, no optimization study has been conducted thus far for the extraction of phenolic compounds from C. zeylanica leaves. Therefore, continuing our interest in natural products, [17][18][19][20][21] the present study focuses on the phytochemical investigation of leaf extract of C. zeylanica using methanol as solvent, UAE (ultrasound-assisted extraction) methodology, and an optimization study employing RSM.…”
Section: Introductionmentioning
confidence: 99%